1. THE ROLE IN MALARIA TRANSMISSION AND HOST PREFERENCE OF VECTORS IN EA SO NATURE RESERVE, EA SO COMMUNE, EA KAR DISTRICT, DAK LAK PROVINCE, 2020-2021 (Vietnam Journal of Community Medicine, 2023)
Objectives: To determine host preference of malaria vectors and malaria parasite infection rate in mosquitoes, entomological inoculation rate in Ea So nature reserve, Ea So commune, Ea Ka district, Dak Lak province.Subjects and methods: The host preference of malaria vectors was determined by an agar gel diffusion method, and the malaria parasite infection rates were found by Real-time PCR, according to the National Institute of Malariology - Parasitology – Entomology standard methods. The entomological inoculation rate was calculated according to WHO (2013) at 4 surveys in June and November 2020, May and December 2021.Results: An. dirus preferred humans, accounting for 100% (15/15), and An. maculatus displayed a preference for cattle accounting for 100% (2/2). However, the results were not enough to evaluate the host preference of mosquito species because of a small sample size, but these results could describe a part of the mosquito biting behavior. P. vivax was detected in An. dirus captured in the deep forest at a rate of 1.59% in 2020 and 0.595% in 2021. An. dirus could transmit malaria in the deep forest habitat. In which entomological inoculation rate in November 2020 was 0.125 and in December 2021 was 0.042.Conclusions: An. dirus had a strong preference for humans and An. dirus had played an essential role in malaria transmission in the deep forest.
Keywords: Malaria, An. dirus, host preference, malaria transmission.